A COMPARATIVE STUDY OF THE CIVIL RIGHTS OF BIOLOGICAL CHILDREN IN THE PERSPECTIVE OF ISLAMIC LAW AND POSITIVE LAW IN INDONESIA - Muhammad Busyra (Universitas Nurul Jadid, 2025)
This study examines the comparison of the civil rights of biological children according to Islamic law and Positive law in Indonesia. The difference of means and perspectives between Islamic Law and Positive Law in Indonesia towards biological children will have an impact on the existence or absence of civil rights for biological children themselves. In Islamic law in Indonesia, biological children only have a nasab relationship with their biological mother and mother’s family. But positive law recognizes a civil relationship with both parents and their families. This research was conducted to answer the need for a more comprehensive material legal rule related to the civil rights of biological children, both in Islamic law and positive law in Indonesia, considering the lack of clear regulations and their impact on people’s lives. The type of research method used in this study is library research, using qualitative research methodology with four approach models, namely statute approach, conceptual approach, analytical approach and comparative approach. This study yielded two main conclusions: first, biological children in Islamic law have only a civil relationship with their mother and her mother’s family. While in Positive law, his status is to have a civil relationship with his father and mother as well as the families of both. Second, in Islamic law, even though a biological child does not have a civil relationship with his biological father, he still has the right to receive living, health, and education expenses as well as the right to obtain property in the form of a mandatory will from his biological father through the institution of ta’zir. While in Positive law, biological children get rights like legitimate children.